A Comparison of Safety and Efficacy between Silodosin Monotherapy Versus Silodosin with Tadalafil add on Therapy in Patients with Benign Prostatic Hyperplasia (Bangladesh Journal of Urology, 2022)
Background: For relieving symptoms of LUTS due to BPH treatment modalities are watchful waiting, medical treatment and surgery. Among medical treatment, options are alpha 1 adrenoreceptor blockers, 5 alpha reductase inhibitors and recently introduced phospodiesterase 5 inhibitors or combination therapy.Objective: To compare the safety and efficacy of silodosin versus silodosin and tadalafil for treating patients with lower urinary tract symptoms secondary to benign prostatic hyperplasia.Materials and Methods: This prospective observational study was conducted in the Department of Urology, BSMMU, Dhaka from April 2020 to March 2021. A total of 66 patients with LUTS due to BPH were selected by purposive sampling on the basis of selection criteria from OPD of Urology, BSMMU. They were randomly divided into two groups: according to odd or even hospital number and label as A group (odd no) and B group (even no). Group-A were provided with silodosin 8.0 mg daily and group-B were provided with silodosin 8.0 mg and tadalafil 5.0 mg daily (B group). Two patients from each group were excluded due to adverse effect and one patients from each group was lost to follow-up. Final analysis was done on sixty patients (30 from each group). The patients were assessed by IPSS, Qmax and PVR. The results were expressed as frequency & percentage (categorical data) and mean ± SD (numerical data). Unpaired t-tests and paired t tests were performed as applicable using SPSS 22.0 and p